Perang Bar Kokhba dan Pergeseran Mesianisme Politis di Kalangan Yahudi - Gandi Wibowo (Voice, 2021)
Misinterpretation of the meaning of the Messiah among the Jews made them repeatedly make mistakes that ended in tragedy. Of the three rebellions in the Judeo-Roman War, the Bar Kokbha war (132-135 AD) brought a change in perspective on the Messiah. The Roman occupation fostered political messianism among the Jews so they expected a Messiah who had military power as their liberator. The impact of the first war (66-70 AD) brought about the collapse of the Temple but the Bar Kokhba war prevented Jews from entering Jerusalem for 3-4 centuries so that the Jewish diaspora was scattered throughout the world. The qualitative approach shows that Rome wanted to remove all Jewish identity as a permanent solution to suppress the Jewish rebellion. Simon bar Kokhba's momentary victory evoked euphoria among the Jews of the coming of the Messiah. They considered Simon bar Kokhba to be the Messiah awaited with confirmation from Rabbi Akiva. But after the revolt was thwarted and humiliated by Rome, there was confusion in the Jewish community. They regard Simon bar Kokhba as a swindler. The understanding of political messianism shifted to post-war eschatological messianism which inflicted heavy losses on the Jews.